To Study the Effect of Plasma Treatment on Fungal Decontamination in wheat and Biochemical Parameters Thereof - Mahey, Nisha (My University, 2016)
In the present study the effect of plasma treatment for surface sterilization and microbial decontamination purposes were studied. Wheat (Triticum aestivum) variety HD3086 was choosen as it is among the major crop being consumed in Northern Hemisphere. The wheat grains were infected with storage fungus Aspergillus flavus (MTCC 817), which is among the most potent fungus. The aflatoxins produced by this fungus causes very deleterious effects. The major problem caused by storage fungi are post harvest losses. Main objective of our study was to diminish the deterioration of crops and grains every year, which helps in reducing a vast economic loss. The SF6 gas was used in plasma reactor for fungal decontamination. The effect of SF6 gas was seen on fungus at different time intervals, to evaluate the minimum duration to destruct the fungal spores present. FTIR analysis was done to compare the difference between the chemical composition of plasma treated and untreated wheat sample. During application of any treatment, it is of prime importance that the treatment should not have any harmful effects, only than it will be considered as ideal treatment. To study the nutritional quality, Proximate analysis were done. Further antioxidant activity and cooking properties were studied to compare the plasma treated and untreated sample. Proximate analysis of the plasma treated sample showed reduction in moisture content value from 9.86% to 8.68%, as the presence of moisture content provides appropriate environment for fungal growth, so reduction in moisture content is an effective result. Cooking time of plasma treated sample was reduced to 6.3 min from 7.4 min which helps in preventing use of resources. Protein profiling was done to compare the Plasma treated and untreated wheat sample by SDS- PAGE. A slight increase in the antioxidant activity of wheat extract is also observed in plasma treated sample.
Master of Technology-Biotechnology
Keywords: Fungal Decontamination; A.flavus; Plasma treatment; Proximate Analysis; Antioxidant activity